"دراسة تحليلية نقدية لكتاب عرفان عبد الحميد فتاح "اليهودية عرض تاريخي والحركات الحديثة في اليهودية = A critical and analytical study of Irfan Abdul Hamid Fattah’s book "Judaism: a historical overview and modern movements in Judaism" = Kajian analitikal-kritikal tentang buku Irfan Abdul Hameed Fattah: “Judaisme: sudut sejarah, gerakan kontemporari dalam Judaisme” - Hasan, Yusof; Shehu, Fatmir (IIUM Press, International Islamic University Malaysia, 2018)
يسعى البحث في هذه الدراسة إلى عرض أحد الكتب الإسلامية التي تتحدث عن تاريخ اليهود على مرِّ العصور، وكما يهدف هذا البحث إلى عرض الكتاب أولاً وتحليل فصوله الخمسة كل على حدة ثانية، ومن ثم يتجه إلى النقد بشقيه الإيجابي والسلبي، ويختم بعد ذلك برأيه الشخصي. وتظهر أهمية هذا البحث جلية في عرض الجهود المبذولة من المؤلف في هذا الكتاب، حيث إن الكتاب يعد شاملاً وعاماً لكثير من أمور اليهود، وكذلك فالمؤلف لم ينل حقه في أن تنشر كتبه ومؤلفاته على نطاق واسع يظهر جهده وغزارة علمه، فيما تتمحور إشكالية البحث في عدم تناول كتاب المؤلف من قبل على وجه العرض والتحليل والنقد، وهذا ما سيسعى هذا البحث إلى فعله ************************************************************* This study seeks to expound one of the Islamic books, which talks about the history of the Jews throughout the ages. The goal of this research is firstly to show the content of the book and secondly to analyze its five chapters separately. It utilizes constructive and destructive criticism, and concludes by showing researcher’s personal view. This study is significant as it shows the exerted efforts of the author in this book. The book is considered comprehensive as well as general in matters related to Jews. Also, the author did not get the right to publish his books and writings on a large scale in order to show his efforts and the abundance of his knowledge. This book has not been discussed before in the form of presentation, analysis and criticism, and this is what this research will attempt to do. *********************************************************** Kajian ini dilhasilkan untuk menjelaskan salah satu penulisan Islamik, yang berbincang mengenai sejarah Yahudi sepanjang zaman. Tujuan kajian ini adalah, pertamanya, untuk membentangkan isi kandungan buku tersebut dan keduanya, untuk menganalisa lima topik dalam buku tersebut secara berasingan. Penyelidikan ini menawarkan kritikan yang membina dan kritikan yang menjatuhkan, kemudian disimpulkan dengan merungkai sudut pandang peribadi penyelidik. Kajian ini adalah signifikan kerana ia memperlihatkan kesungguhan yang dikerah penulis buku ini. Buku tersebut merupakan penulisan yang menyeluruh dan umum tentang isu-isu yang berkaitan dengan Yahudi. Tambahan lagi, penulis tersebut telah dinafikan haknya untuk menerbitkan buku dan penulisannya dalam skala besar bagi membuktikan kesungguhan dan ilmunya yang tinggi. Buku ini tidak pernah dibincangan dalam bentuk pembentangan, analisa dan kritikan, maka atas tujuan inilah kajian ini dihasilkan.